Abdominal Cerclage in Twin Pregnancy after Radical Surgical Conization - Ioannis Kyvernitakis; Fred Lotgering; Birgit Arabin (Hindawi Limited, 2014)
Radical and repeated cone biopsies are associated with a high risk of spontaneous preterm birth. A 30-year-old gravida 1 presented with a spontaneous dichorionic twin pregnancy. She had a history of two radical surgical conizations. By speculum examination, no cervical tissue was detected. A history-indicated transabdominal cervicoisthmic cerclage was performed at 12 + 4/7 gestational weeks because of assumed cervicoisthmic insufficiency. The pregnancy continued until 34 + 3/7 weeks when the patient developed preeclampsia indicating Cesarean delivery. Transabdominal cerclage in twin pregnancy has rarely been described, but it may be considered in case of extreme cervical shortening after radical cervical surgery, as it would in singleton pregnancy.